Silver Linings in the Face of Temptations: How Mixed Emotions Promote Self-Control Efforts in Response to Goal Conflict - Berrios-Espinoza, R (Springer New York LLC, 2018)
Choosing between conflicting goals is a frequent yet difficult problem, especially when temptations are involved because self-control effort is required to overcome them. This study investigated whether experiencing mixed emotions in response to goal conflict can facilitate the necessary self-control effort needed to resist temptations. A sample of 73 individuals participated in an intensive longitudinal study, completing several measures 4 times a day during ten consecutive days, producing over 2500 observations. Results derived from using multilevel structural equation modeling confirmed that mixed emotions mediated the relationship between perceived goal conflict and intentions to resist temptations, over and above the influence of single positive emotions or negative emotions, and trait levels of self-control. Implication of these findings for collaboration and the impact of mixed emotions in more general social dilemmas are explored. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.